Effects of anaerobic exercise and detraining on the caspase-3 expression of rat ventricular cardiomyocyte (Medical Journal of Indonesia, 2015)
Background: Anaerobic physical exercise is a high intensity physical exercise performed in a short time. This exercise can stimulate apoptosis in left ventricular cardiomyocytes. The aim of this study is to analyze the apoptosis of cardiomyocytes after anaerobic exercise and detraining. Methods: Thirty two wistar rats Ratus Novergicus 250-350 grams (8-10 weeks old) were divided into the following groups (n = 4) and given naerobic physical exercise four and 12 weeks (group Exc-4, Exc-12) and anaerobic exercise followed by four weeks of detraining (Exc-4-D, Exc-12-D). The control groups were only observed in the same period (group CTL-4, CTL-12, CTL-4-D, CTL-12-D). At the end of observation, the rats were sacrificed and examination of the expression of caspase-3 as an indicator of apoptosis was done using immunohistochemical staining. Data were analyzed with ANOVA test. Results: An increase in expression of caspase-3 in the group Exc-4 (72.03%) compared to the CTL-4 (27.22%), (p < 0,001); and Exc-12 (79.30%) compared to the CTL-12 (30.53%) (p = 0.027). Detraining process showed a significant decline Capase-3 expression (31.12% in exc-4-D and 30.44% in the exc-12-D). Conclusion: Anaerobic physical exercise can increase apoptosis in rat left ventricle cardiomyocyte characterized by increased expression of caspase-3. Detraining can improve heart condition characterized by decreased expression of caspase-3.